The Role of Savings and Lending Groups in the Financial Inclusion of Rural Women Entrepreneurs: A Case Study of IMPABARUTA Cooperative in Kamonyi District, Rwanda. - Mukamwezi, Albertine; Ocan, Johnson; Adyanga, Francis Akena (Kabale University, 2025)
This article examined the role of savings and Lending Groups (SLGs) in promoting small business creation among rural women entrepreneurs, using IMPABARUTA Cooperative in Kamonyi district. It is aimed at assessing how SLGs facilitate the establishment and growth of small enterprises, and how they impact women’s access to financial resources. A descriptive research design was employed to explore the role of SLGs. A purposive sampling method was used to select 200 respondents from 408 Cooperative women members. Structured questionnaires, semi-structured interviews, and document reviews were used for data collection. The main findings revealed the transformative role of savings and lending groups in promoting financial inclusion among rural women in Kamonyi District, Rwanda. A paired t-test revealed significant increases in savings (from 50,000 Rwf to 500,000 Rwf) and loan access (from 10% to 80%) after joining the IMPABARUTA Cooperative. The statistical results underscore the groups’ effectiveness in enhancing financial habits and credit availability. These changes economically empower women, allowing them to invest in enterprises and promote broader community development, particularly in underdeveloped rural areas. Further, challenges such as trust issues,